STRATEGI PEMBELAJARAN MATEMATIKA PADA ANAK USIA DINI DALAM PENGEMBANGAN KECERDASAN KINESTETIK - Alex Haris Fauzi; Firma Yudha; Nurul Fatimah (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Mathematics is one of the branch of science which often applied in daily life , good in the implementation, practical needs , or developed other of earth sciences division. The role of math is very important, math taught so early on, namely in early childhood , are taught with how to play. Methods used in this research is qualitative descriptive , a subject in this research is that the school is paud , one of them is paud dhiva located in the village Karangsari, kecamatan Sempu, kabupaten Banyuwangi, as the number of students 18 student. Data retrieval techniques use observation, documentation, and interviews. Checking the validity of data using source triangulation. A strategy of learning the math on early childhood in the development of intelligence in a kinesthetic piaud dhiva school includes: coordination, balance, strength, and flexibility. Of research being done can be concluded that teacher strategy piaud dhiva school in developing a kinesthetic intelligence in learning of mathematics in the category that is by train, good guiding, motivate, stimulant, as well as lean on kids to get the child has a kinesthetic intelligence good by 4 aspects had been determined.